Traditional management of ancient Pu'er teagardens in Jingmai Mountains in Yunnan of China, a designated Globally Important Agricultural Heritage Systems site - Wanlin Li; Qing Zhang; Yanxiao Fan; Zhuo Cheng; Xiaoping Lu; Binsheng Luo; Chunlin Long (BMC, 2023)
Abstract Background Pu'er Traditional Tea Agroecosystem is one of the projects included in the United Nations' Globally Important Agricultural Heritage Systems (GIAHS) since 2012. Against the background of having rich biodiversity and a long history of tea culture, the ancient tea trees in Pu'er have experienced from wild-transition-cultivation for thousands of years, and the local people's knowledge about the management of ancient teagardens has not been rigorously recorded. For this reason, it is important to study and record the traditional management knowledge of Pu'er ancient teagardens and the influence on the formation of tea trees and communities. This study focuses on the traditional management knowledge of ancient teagardens in Jingmai Mountains, Pu'er, and monoculture teagardens (monoculture and intensively managed planting base for tea cultivation) were used as the control, through the community structure, composition and biodiversity of ancient teagardens to respond to the influence of traditional management, and this work with a view to providing a reference for further research on the stability and sustainable development of tea agroecosystem. Methods From 2021 to 2022, information on traditional management of ancient teagardens was obtained through semi-structured interviews with 93 local people in the Jingmai Mountains area of Pu'er. Informed consent was obtained from each participant before conducting the interview process. The communities, tea trees and biodiversity of Jingmai Mountains ancient teagardens (JMATGs) and monoculture teagardens (MTGs) were examined through field surveys, measurements and biodiversity survey methods. The Shannon-Weiner (H), Pielou (E) and Margalef (M) indices were calculated for the biodiversity of the teagardens within the unit sample, using monoculture teagardens as a control. Results The tea tree morphology, community structure and composition of Pu'er ancient teagardens are significantly different from those of monoculture teagardens, and the biodiversity is significantly higher than that of monoculture teagardens. The local people mainly manage the ancient tea trees mainly using several methods, including weeding (96.8%), pruning (48.4%) and pest control (33.3%). The pest control mainly relies on the removal of diseased branches. JMATGs annual gross output is approximately 6.5 times that of MTGs. The traditional management of ancient teagardens is through setting up forest isolation zones as protected areas, planting tea trees in the understory on the sunny side, keeping tea trees 1.5-7 m apart, as well as consciously protecting forest animals such as spiders, birds and bees, and reasonably rearing livestock in the teagardens. Conclusions This study shows that local people have rich traditional knowledge and experience in the management of ancient teagardens in Pu'er, and that this traditional management knowledge has impacted the growth of ancient tea trees, enriched the structure and composition of tea plantation communities and actively protected the biodiversity within ancient teagardens.